1999
DOI: 10.1093/humrep/14.5.1328
|View full text |Cite
|
Sign up to set email alerts
|

HOX gene expression is altered in the endometrium of women with endometriosis

Abstract: HOXA10 and HOXA11 are homeobox genes that function as transcription factors essential to embryonic development. We have recently described a role for each of these two genes in regulating endometrial development in the adult during the course of a menstrual cycle. Both Hoxa10 and Hoxa11 are essential for implantation in the mouse and appear to play a similar role in women. To investigate the role of HOX genes in the endometrium of women with endometriosis, quantitative Northern blot analysis was performed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
247
1
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(263 citation statements)
references
References 30 publications
9
247
1
6
Order By: Relevance
“…Hoxa10 antisense treatment reduces maternal Hoxa10 expression and reduces litter size, demonstrating that maternal Hoxa10 is necessary for endometrial receptivity to blastocyst implantation. Similarly, in humans with endometriosis and decreased implantation rates, maternal uterine HOXA10 is also decreased (Taylor et al, 1999). This finding suggests a similar role in human endometrial development and receptivity to implantation.…”
Section: Introductionmentioning
confidence: 62%
“…Hoxa10 antisense treatment reduces maternal Hoxa10 expression and reduces litter size, demonstrating that maternal Hoxa10 is necessary for endometrial receptivity to blastocyst implantation. Similarly, in humans with endometriosis and decreased implantation rates, maternal uterine HOXA10 is also decreased (Taylor et al, 1999). This finding suggests a similar role in human endometrial development and receptivity to implantation.…”
Section: Introductionmentioning
confidence: 62%
“…6 However, indirect evidence has suggested a role for maternal Hoxa10 expression in implantation. 10,14 We have previously shown that four genes of the HOXA cluster demonstrate continued expression in the adult reproductive tract. 5 Furthermore, we have shown that HOXA10 is expressed in the adult endometrium in a dynamic way that varies with the menstrual cycle suggesting a role for maternal HOXA10 in implantation.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that, based on the rise in HOXA10 expression at the time of implantation, maternal HOXA10 is probably similarly required for this process in women. 7,10 The alteration of human HOXA10 expression in the adult endometrium is a potential contraceptive agent or fertility treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the expression of both HOXA10 and HOXA11 rises dramatically during the implantation window and remains elevated throughout the secretory phase. However, patients with endometriosis do not show this rise in HOXA10 and HOXA11 (Taylor et al 1999a;Kim et al 2007;Lee et al 2009). …”
Section: Hox Genes and Endometriosismentioning
confidence: 94%